Clarifying the value relevance of voluntary carbon reporting: The case of Malaysian carbon-intensive industries - Rahman N.R.A.; Rasid S.Z.A.; Basiruddin R. (Inderscience Publishers, 2023)
Climate change; Earnings; Global warming; Greenhouse gases; Regression analysis; Carbon reporting; Content analysis; Earnings per share; Malaysians; Panel data; Return on assets; Return on equity; Value relevances; Carbon; accountability; carbon emission; equity; global warming; greenhouse gas; guideline; industrial emission; market conditions; panel data; standard (regulation); Malaysia